Utilizing Wordwall as A Media Learning in Enhancing Students’ Vocabulary : Students’ Perception - Nurul Fadhilah; Sholihatul Hamidah Daulay (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to explore students’ perceptions of the use of Wordwall as a digital media tool to enhance vocabulary learning in English classrooms. As vocabulary is a crucial component in language acquisition, interactive and engaging media such as Wordwall are expected to improve student learning outcomes and motivation. The participants of this study were five seventh-grade students from a junior high school, selected using purposive sampling based on their experience using Wordwall during English lessons. This research employed a qualitative approach with a phenomenological design to gain an in-depth understanding of students’ subjective experiences. Data were collected through participant observation, questionnaires, and semi-structured interviews. The questionnaire was based on three constructs from the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2): performance expectancy, effort expectancy, and hedonic motivation. Data were analyzed thematically by identifying patterns, formulating meaning, and describing the essence of the participants’ experiences. The findings reveal that students generally perceive Wordwall positively. Most participants stated that Wordwall made vocabulary learning more enjoyable and helped them memorize new words faster (performance expectancy). They also found it relatively easy to use after guidance from the teacher (effort expectancy) and expressed that the learning process felt more like a game than a traditional classroom activity (hedonic motivation). However, some students experienced initial confusion with the interface and game rules. Overall, the use of Wordwall created a more engaging and motivating learning environment, supporting vocabulary development through interactive digital learning experiences. Keywords: digital media; interactive learning; students’ perception; vocabulary learning; Wordwall